Re-Actualization Balinese Gamelan Harmony for Renewal Knowlegde of the Balinese Music - I Ketut Ardana (IJCAS (International Journal of Creative and Arts Studies), 2021)
Balinese music has a variety of gamelan that develops in the community. Balinese gamelan is a central object in the development of Balinese musical knowledge. One of the most problematic is the harmony system. In the context of Balinese music knowledge, the harmony system is an element that is often discussed its existence. The 'harmony system' has been recognized through the dualistic concept. This concept is the source of the technique for playing the Balinese Gamelan. Knowledge of the harmony system with this dualistic concept is based on the object of research by Gamelan Gong Kebyar. Gamelan Gong Kebyar is indeed very closely related to the dualistic system. However, this system is not relevant to several other Balinese Gamelan, one of which is the Gamelan Gambang. Therefore, knowledge of the harmony system in Balinese music needs to be updated. This update is an actualization of knowledge about gamelan harmony. The problems discussed in this article are what is Balinese Gamelan harmony, what is the roles of Balinese Gamelan harmony and the concept of Balinese musical harmony. This reaserch uses a mix method, namely qualitative and quantitative methods. Musicology approach as a qualitative method while sound physics as a quantitative method. Re-aktualisasi Harmoni Gamelan Bali untuk Pembaruan Pengetahuan Musik Bali Abstrak Karawitan Bali memiliki ragam gamelan yang berkembang di masyarakat. Gamelan Bali merupakan objek sentral dalam pengembangan pengetahuan karawitan Bali. Salah satu yang paling bermasalah adalah sistem harmoni. Dalam konteks pengetahuan karawitan Bali, sistem harmoni merupakan unsur yang sering dibicarakan keberadaannya. Sistem harmoni terepresentasi melalui konsep dualistik. Konsep inilah yang menjadi sumber teknik memainkan Gamelan Bali pada umumnya. Pengetahuan sistem harmoni dengan konsep dualistik ini berdasarkan objek penelitian Gamelan Gong Kebyar. Gamelan Gong Kebyar memang sangat erat kaitannya dengan sistem dualistik. Namun sistem ini tidak relevan dengan beberapa Gamelan Bali lainnya, salah satunya Gamelan Gambang. Oleh karena itu, pengetahuan tentang sistem harmoni dalam karawitan Bali perlu dimutakhirkan. Pembaruan ini merupakan aktualisasi pengetahuan tentang harmoni gamelan. Permasalahan yang dibahas dalam artikel ini adalah apa yang dimaksud dengan harmoni Gamelan Bali, batasan harmoni Gamelan Bali dan model harmoni secara musikal gamelan Bali. Penelitian ini menggunakan mixmethode , yaitu metode kualitatif dan kuantitatif. Pendekatan musikologi sebagai metode kualitatif sedangkan fisika bunyi sebagai metode kuantitatif.